Clinical outcome of porous hydroxyapatite/collagen graft on bone defects following curettage of bone tumors. Issue 10 (19th April 2022) - Iwatsu, Jun; Watanuki, Munenori; Yoshida, Shinichirou; Hitachi, Shin; Watanabe, Mika; Aizawa, Toshimi
Abstract: Hydroxyapatite/collagen (HAp/col) has been reported to be a highly useful bone‐like nanocomposite. This study included 33 human patients to investigate the details of the clinical outcomes, which are (1) onset of timing of bone regeneration, (2) replacement by regenerated bone of HAp/col and (3) complications, in human cases grafting HAp/col in large bone defects, following curettage of bone tumors. Porous HAp/col initiated bone regeneration approximately 59 days following the surgery. In 15 cases (45%), complete replacement by newly formed bone was observed 12 months after surgery. On the other hand, incomplete replacement of HAp/col at the final follow‐up was observed in 13 cases (39%). In these cases, HAp/col could not be detected in the transparent area of postoperative plain radiographs owing to quick absorption; moreover, it was difficult to distinguish whether the transparent area in plain radiographs was remaining HAp/col, recurrence, or remaining tumor. In addition, larger HAp/col implantation volume (≧15 cm 3 ) was associated with poorer result of complete replacement (log‐rank, p = .005). Further studies are warranted for the construction of a new artificial bone graft substitute that is more quickly and surely regenerated by newly formed bone in large bone defects.